Pengaruh Model Pembelajaran Berbasis Teknologi Informasi terhadap Hasil Belajar Mahasiswa Pendidikan Agama Kristen - Claudina Margarida Freitas Belo; Harun Y. Natonis (Pengharapan : Jurnal Pendidikan dan Pemuridan Kristen dan Katolik, 2025)
This study analyzes the influence of information technology (IT)-based learning models on the learning outcomes of Christian Religious Education (PAK) students. In the digital era, PAK is required to adapt in order to shape the character and spirituality of students. Using a qualitative literature study of the literature, it was found that models such as e-learning, blended learning, AI, interactive multimedia, and advanced LMS significantly improve learning outcomes. This improvement is driven by the flexibility of material access, motivation via interactivity and personalization, global collaboration, and the development of digital literacy and Christian ethics. Despite infrastructure and competency challenges, the strategic implementation of IT learning models has been proven to transform the PAK learning process, contributing to improving students' cognitive, affective, and psychomotor achievements.